Pergament oder: Was haben Tiere jemals für uns getan? - Michael Becht (Institut für Bibliothekswissenschaft Berlin, 2020)
This article tries to offer a new perspective on parchment, mainly with regard to animals whose skins were, and sometimes still are, used to manufacture this writing material. A short outline of the manufacturing process serves as a basis and is complemented by a similarly short history of development and usage. Subsequently, some calculations, which should not be taken too seriously, may illustrate the huge number of animals that had to be slaughtered to produce enough parchment for all the codices in the older collections of our libraries. The second main topic is the animals who served as the main source for parchment during the German Middle Ages, namely sheep, goats and cattle. Therefore aspects of zooarchaeology and agricultural history are brought up here as well.